2010
DOI: 10.1177/1420326x10373330
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation Rates and Unsatisfied Percentage from Indoor CO2 Concentration

Abstract: This work reports the results of a survey carried out on a hall in a historic building in Palermo (Italy) with the aim of assessing the air quality by means of objective measurement of carbon dioxide (CO 2 ) concentration and its subjective evaluation through a questionnaire. The measured values of CO 2 concentration were compared with those evaluated using the Meckler equation under steady-state conditions, having verified necessary parameters such as the constancy of the indoor and outdoor CO 2 levels and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Therefore, CO 2 is used as a measure of indoor air pollution [15]. Earlier research has shown that CO 2 concentration could play a role as a surrogate indicator ofIAQ and ventilation efficiency [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CO 2 is used as a measure of indoor air pollution [15]. Earlier research has shown that CO 2 concentration could play a role as a surrogate indicator ofIAQ and ventilation efficiency [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, under the same ventilation conditions, the elderly are more dissatisfied with the air quality than the young. 41 Due to physiological differences, the elderly are often troubled by dry skin caused by uncomfortable indoor hot and humid environment. 42 The same is true for the elderly in the RCFs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there are domestic electricals (e.g., cooker and fridge), household items (e.g., taps, bed and sofa), temperature handling devices (e.g., air conditioning, radiators) etc. The benefits of these devices may consist in: (1) raising safety and security by monitoring lifestyle patterns or the behaviours and providing support, should a possibly harmful situation occur; (2) providing comfort by controlling temperature and ventilation [21,22] automatically; (3) enhancing economy by adjusting unused lights [19].…”
Section: Smart Home Servicementioning
confidence: 99%